(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
The polymer hypromellose (HPMC) is widely used for 3D printing of pharmaceutical dosage forms. This paper deals with the study of acceleration of drug release from 3D printed HPMC tablets. Polyvinylpyrrolidone (PVP) was added and the infill of the tablets was also varied. Both, lower infill and addition of PVP, can accelerate the drug release of caffeine from 3D printed HPMC tablets.